Psychiatric Aspects of Lichen Simplex Chronicus: A Systematic Literature Review - Rahmadini, Meirina (Scientia Psychiatrica, 2023)
Introduction: Lichen simplex chronicus (LSC) is an eczematous skin condition characterized by thickened and 'lichenified' skin plaques. The involvement of psychological variables and transitory alleviation of pruritus following vigorous scratching appears to be critical in the development and maintenance of its course. Methods: The literature search process was carried out on various databases (PubMed, Web of Sciences, EMBASE, Cochrane Libraries, and Google Scholar) regarding risk factors and clinical overview of acute kidney injury. The search was performed using the terms: (1) " psychiatric factors" OR "psychological factors" OR "stress" AND (2) "lichen simplex chronicus". Results: Studies and literature have described the relationship between skin lesions exacerbation and the level of psychopathological conditions in response to stress. Pruritus or itch is the most prominent symptom of LSC, which seems to have a marked psychological component. Conclusion: Psychiatric factors have a role in both the onset and persistence of this form of neurodermatitis.